2017
DOI: 10.1177/0300060516685204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of Chinese patients with 21-hydroxylase deficiency and analysis of genotype–phenotype correlations

Abstract: ObjectiveThe spectrum of molecular defects in Chinese patients with 21-hydroxylase deficiency (21-OHD), and genotype–phenotype relationships are unknown.MethodsWe screened eight patients with non-classical (NC) 21-OHD and 35 with classical 21-OHD, and detected nine known mutations.ResultsThe most frequent mutation among the 43 21-OHD cases was p.Ile172Asn (allele frequency, 36.0%), followed by c.290-13A/C > G (20.9%), Del (8.6%), p.Pro30Leu (7.0%), p.Gln318Ter (7.0%), p.Val281Leu (4.7%), p.Arg356Trp (2.3%), p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Among our 21-OHD CAH patients, the most prevalent CYP21A2 variants were c.293-13C > G (31.36%), Del (18.64%), p.I173N (16.95%), E3 Δ8 (5.08%), p.R483PfsX58 (4.24%) and p.R357W (3.39%). The rst three variants, c.293-13C > G, Del and p.I173N, were consistent with the most frequent variants in the Asian population [13][14][15][16][17]; however, our data showed higher E3 Δ8 and p.R483PfsX58 variant prevalence rates and a lower p.R357W variant prevalence. Ethnic differences were evident among different studies; the frequencies of p.P31L and p.V282L were 1.69% and 0.85% in our study, respectively, while the p.V282L…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Among our 21-OHD CAH patients, the most prevalent CYP21A2 variants were c.293-13C > G (31.36%), Del (18.64%), p.I173N (16.95%), E3 Δ8 (5.08%), p.R483PfsX58 (4.24%) and p.R357W (3.39%). The rst three variants, c.293-13C > G, Del and p.I173N, were consistent with the most frequent variants in the Asian population [13][14][15][16][17]; however, our data showed higher E3 Δ8 and p.R483PfsX58 variant prevalence rates and a lower p.R357W variant prevalence. Ethnic differences were evident among different studies; the frequencies of p.P31L and p.V282L were 1.69% and 0.85% in our study, respectively, while the p.V282L…”
Section: Discussionsupporting
confidence: 84%
“…Surprisingly, we found that 8.47% (5/59) of the patients clinically presented with the SW (n = 4) and NC (n = 1) phenotypes without biallelic variants (Supplement Table 3). Studies have reported that the monoallelic variant and absent variants accounted for 2.2-24% of enrolled children [10,16,[19][20][21]26].…”
Section: Discussionmentioning
confidence: 99%
“…Our global genotype–phenotype correlation was 92.4%, slightly higher than the average worldwide genotype–phenotype correlation, estimated in 80–90% [10, 11, 43]. Usually, the correlation is higher than 80–90% for the pathogenic variants associated with low enzymatic activity and a SW phenotype (groups 0 and A) and for the pathogenic variants of the group C (NC phenotype), but lower for the group B pathogenic variant (usually associated with a SV phenotype) [6, 9, 11-13, 24, 39, 44-46].…”
Section: Discussionmentioning
confidence: 58%
“…It is worth mentioning that four out of five patients with P30L had clitoromegaly compared with none of those carrying other NC mutations (e.g., V281L) [53]. Clitoromegaly was also reported in NC patients carrying P30L in China [55]. This shows that the P30L mutation, although the enzyme activity is preserved sufficiently, causes a more severe form of NC or even a SV form.…”
Section: Molecular Structure Of P30l Mutation and Functional Analysismentioning
confidence: 96%